Information interaction between the Federal Service for Alcohol and Tobacco Market Control and executive authorities as a condition for the effectiveness of state control (supervision) ("Journal "U". Economy. Management. Finance.", 2026)
The article examines how Rosalkogoltabakkontrol's information interaction with executive authorities and the use of digital systems increase the effectiveness of state control over the circulation of excise goods and excise revenues, as well as the necessity of further digital integration and the implementation of predictive analysis.
Keywords: state control; supervision; information interaction; Rosalkogoltabakkontrol